KEDUDUKAN FATWA MAJELIS ULAMA INDONESIA (MUI) DALAM PERSPEKTIF HUKUM ISLAM DAN NASIONAL: STUDI IMPLIKASI FATWA TERHADAP MASYARAKAT - Imaro Sidqi; Doli Witro (Postgraduate State Islamic Institute (IAIN) Metro, 2020)
This article discusses the existence of MUI fatwa and its position in Indonesia. So far, people are more likely to use the fatwa law than national law. Many political interests, so that the independence of the fatwa in Indonesia, the MUI fatwa, is doubtful of its integrity. In the context of Islamic law, a fatwa is an essential presence in society, while in national law, a fatwa is only a doctrine whose status is not required to be followed. The deficient legal awareness of the community is a problem in the community because the political influence of the fatwa has a negative impact, so it is feared that it will create a negative thing that lives and develops into a civilization in society. From this writing, it can be concluded that the position of the fatwa is not required to be followed so that public awareness about the law must be socialized by the government so that people can understand. However, if the fatwa is following the constitution, the fatwa can be applied in the law so that the fatwa is not easy to be politicized by any party concerned.